SIMULATION-BASED LEARNING IN MARITIME TRAINING: ENHANCING COMPETENCY AND PREPAREDNESS - Asman Ala; Nazilul Hamidi; Siska Yoniessa; Fitri Masito; Muhammad Abdul Muis (Meteor STIP Marunda, 2024)
Simulation-Based Learning (SBL) is a pivotal component in maritime education, offering realistic and immersive experiences for cadets. This research critically evaluates SBL's efficacy among 30 cadets undergoing vocational practice or internships, aligning with International Maritime Organization (IMO) - Standards of Training, Certification, and Watchkeeping (STCW). Through qualitative analysis, SBL was found to significantly enhance cadets' competency, decision-making skills, and confidence in handling maritime challenges. Challenges such as technical issues and fidelity discrepancies were noted, underscoring the need for ongoing improvement. Furthermore, the study emphasizes the importance of aligning maritime education with international standards to ensure standardized and comprehensive training. The findings contribute to the discourse on SBL's role in maritime education, highlighting its potential to prepare cadets for real-world scenarios effectively.